Realization of individual-personal development potential of children with intellectual disabilities in the process of adaptive physical education - Parfenova L.A.; Timoshina I.N.; Burtseva E.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determination of the leading principles of adaptive physical education aimed at realizing the individual development potential of students with intellectual disabilities. Methods and structure of the study. A theoretical analysis of scientific and methodological literature in the field of adaptive physical education on the psychological and pedagogical characteristics of children with intellectual disabilities was carried out. Results and conclusions. The concept of «individual-personal development potential of children with intellectual disabilities» is formulated as a set of their biological-individual and personal-social characteristics that make it possible to realize what is inherent in nature (physical abilities, functional capabilities and mental (cognitive) processes) and to form socially necessary qualities in the process of various activities. General pedagogical and specific principles of adaptive physical education are identified, which make it possible to realize the individual and personal development potential of children with intellectual disabilities.